Direct tensile testing of Self-Compacting Concrete. (1st June 2016) - Alhussainy, Faez; Hasan, Hayder Alaa; Rogic, Sime; Neaz Sheikh, M.; Hadi, Muhammad N.S.
Abstract: This study explores a new procedure to determine the stress-strain behaviour of Self-Compacting Concrete (SCC) under direct uniaxial tension. Special steel claws were designed, built and installed at both ends of 100 × 100 × 500 mm SCC specimens. These claws were used to transfer the applied tensile forces to the specimens. The cross-section of the specimens was reduced in the middle to ensure that failure would occur in the middle. The specimens were tested at 28 days for direct tensile stress-strain behaviour as well as for compressive, splitting and flexural strengths. The test results showed that there was no slippage or fracture at the ends of any of the specimens. Also, the failure occurred in the middle of specimens, as expected. The direct tensile strength of the specimens was found to be lower than the splitting and flexural strengths.